HYBRID CLOUD INFRASTRUCTURE AND OPERATIONS EXPLAINED accelerate your application migration and modernization journey on cloud the cloud with IBM and Red Hat - HABIBA, MANSURA (PACKT PUBLISHING LIMITED, 2022)
Modernize and migrate smoothly to hybrid cloud infrastructure and successfully mitigate complexities relating to the infrastructure, platform, and production environment Key Features Presents problems and solutions for application modernization based on real-life use cases Helps design and implement efficient, highly available, and scalable cloud-native applications Teaches you how to adopt a cloud-native culture for successful deployments on hybrid cloud platforms Book Description Most organizations are now either moving to the cloud through modernization or building their apps in the cloud. Hybrid cloud is one of the best approaches for cloud migration and the modernization journey for any enterprise. This is why, along with coding skills, developers need to know the big picture of cloud footprint and be aware of the integration models between apps in a hybrid and multi-cloud infrastructure. This book represents an overview of your end-to-end journey to the cloud. To be future agnostic, the journey starts with a hybrid cloud. You'll gain an overall understanding of how to approach migration to the cloud using hybrid cloud technologies from IBM and Red Hat. Next, you'll be able to explore the challenges, requirements (both functional and non-functional), and the process of app modernization for enterprises by analyzing various use cases. The book then provides you with insights into the different reference solutions for app modernization on the cloud, which will help you to learn how to design and implement patterns and best practices in your job. By the end of this book, you'll be able to successfully modernize applications and cloud infrastructure in hyperscaler public clouds such as IBM and hybrid clouds using Red Hat technologies as well as develop secure applications for cloud environments. What you will learn Strategize application modernization, from the planning to the implementation phase Apply cloud-native development concepts, methods, and best practices Select the right strategy for cloud adoption and modernization Explore container platforms, storage, network, security, and operations Manage cloud operations using SREs, FinOps, and MLOps principles Design a modern data insight hub on the cloud Who this book is for This book is for cloud-native application developers involved in modernizing legacy applications by refactoring and rebuilding them. Cloud solution architects and technical leaders will also find this book useful. It will be helpful to have a basic understanding of cloud-native application development and cloud providers before getting started with this book.